STUDI KELAYAKAN AIR TANAH UNTUK KEBUTUHAN AIR MINUM DI KELURAHAN ROMANG POLONG KECAMATAN SOMBA OPU KABUPATEN GOWA - Destiquama, Destiquama; Hasriyanti, Hasriyanti; Amal, Amal (UNIVERSITAS NEGERI MAKASSAR, 2019)
The quality of ground water for drinking water needs is based on physical, chemical and biological parameters of Romang Polong. The researcher took 5 kinds of water as samples based on land use by applying the Storet method. The water sample was tested in the field and analyzed in the laboratory. The results obtained are compared with the specified based on criteria of water quality which indicated that groundwater in the Romang Polong is suitable to be used as drinking water quality standards at the point 2, 3, and 4. However, at the point 1 and 5 are not feasible to be used as drinking water quality standards. But, it is still feasible to use for household needs such as bathing and washing. It might be happened because the physical, chemical, and biological parameters exceeded the maximum permissible threshold based on the drinking water quality standard according to Minister of Health of the Republic of Indonesia No. 492 / MENKES / PER / IV / 2010.